Development of Canva-Based E-Modules to Improve Motivation and Learning Outcomes of Students on the Core Topic of Acids and Bases - Afdhalifayanti Hamdjah; Muhammad Anwar; Sudding Sudding (Postgraduate, University of Mataram, 2026)
This study is a Research and Development (R&D) project aimed at producing a Canva-based e-module that is valid, practical, and effective, and capable of enhancing students’ motivation and learning outcomes in the subject of acids and bases. The model used is the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. The research subjects consisted of 36 eleventh-grade students at State Senior High School 8 Bulukumba for the 2026/2027 academic year. The feasibility of the e-module was assessed based on three criteria: validity, practicality, and effectiveness. The research results indicate that: 1) the validity of the e-module, as assessed by two expert validators, received an average score of 3.56, falling into the “highly valid” category; 2) the practicality of the e-module in terms of the feasibility of implementation received a score of 1.86, falling into the “fully implemented” category; in terms of teacher feedback, it received an average of 93.54%, classified as “highly practical”; and the average student response score was 89.78, also classified as “highly practical,” 3) The Canva-based e-module is considered effective based on the percentage of students’ learning motivation, which increased from 62.85% to 87.15%—falling into the “very high” category—and student learning outcomes met the criteria for effectiveness, with a class mastery rate of 91.67%. This indicates that the Canva-based e-module is valid, practical, and effective in improving students’ motivation and learning outcomes in acid-base material